TLR4 Targeting as a Promising Therapeutic Strategy for Alzheimer Disease Treatment - Zhou, Yongji; Chen, Yanxing; Xu, Congcong; Zhang, Hao; Lin, Caixiu (Frontiers in Neuroscience, 2020)
Alzheimer disease (AD) is a devastating neurodegenerative disorder characterized by extracellular accumulation of amyloid-beta and formation of intracellular neurofibrillary tangles. Microglia activation and neuroinflammation play important roles in the pathogenesis of AD; Toll-like receptor 4 (TLR4)—a key component of innate immune system—in microglia is also thought to be involved based on the observed association between TLR gene polymorphisms and AD risk. TLR4 has been shown to exert both detrimental and beneficial effects on AD-related pathologies. In preclinical models, experimental manipulations targeting TLR4 were shown to improve learning and memory, which was related to inhibition of proinflammatory cytokine release and reduction of oxidative stress. In this review, we summarize the key evidence supporting TLR4 as a promising therapeutic target in AD treatment.